Art & trousers tradition and modernity in contemporary Asian art - Elliott, David, 1949- (Artasiapacific Foundation, 2021)
"An illustrated collection of more than thirty essays and 640 color images, Art and Trousers moves deftly between regional analysis, portraits of individual artists, and a metaphorical history of trousers. This book presents a panoramic view of modern and contemporary Asian art, varying its focus on the impacts of invention, tradition, exchange, colonization, politics, social development, and gender. David Elliott spotlights the practice of many leading global artists of the early twenty-first century, including Hiroshi Sugimoto, Cai Guo-Qiang, Ai Weiwei, Xu Bing, Rashid Rana, Bharti Kher, Makoto Aida, Chatchai Puipia, and Yeesookyung, among many others. Art and Trousers offers insight into the development of a key curatorial practice for our times, and it will be an essential resource for anyone seeking to understand contemporary art and the way it operates across borders"--Publisher's website.